Transfer of Arabic formulaic courtesy expressions used by advanced Arab learners of Spanish - Cuesta, Ana Ramajo (2015)
In Spain and Arab countries, the way of celebrating feasts and occasions is gathering with family and enjoying a meal together. In this communicative situation, compliments on the delicious food prepared will take place. The purpose of the study is analyzing compliment/compliment responses used by advanced Arab learners of Spanish (C1) with an advanced knowledge of English and French (C1 level). In order to compare this speech act with the native production, the researchers considered three groups of participants: native speakers of Spanish, native speakers of Arabic and Lebanese learners of Spanish. The research variable is " origin " . " Gender " and " age " variables are not included in this study. A muted video is the instrument to collect the data. Compliment/compliment responses in Arabic and Spanish are analyzed following a taxonomy created by the researchers. In Spanish, explanations were used, whereas in Arabic the use of formulaic courtesy expressions was frequent. In the production of Lebanese learners of Spanish, pragmatic transfer of Arabic formulaic expressions and the influence of foreign languages (French and English) occur.